RECENT ADVANCES ON OBESITY INDUCED DIABETES - Jain, Deepak (International Journal of Pharmaceutical & Biological Archive, 2017)
The relationship between obesity and diabetes is of such interdependence that the term ’diabesity’ has been coined. The passage from obesity to diabetes is made by a progressive defect in insulin secretion coupled with a progressive rise in insulin resistance. Both insulin resistance and defective insulin secretion appear very prematurely in obese patients, and both worsen similarly towards diabetes. Thus, the classic ’hyperbolic relationship’ between insulin resistance and insulin secretion and the ’glucose allostasis concept’ remain prevailing concepts in this particular field of knowledge. An increase in overall fatness, preferentially of visceral as well as ectopic fat depots, is specifically associated with insulin resistance. The accumulation of intra myocellular lipids may be due to reduced lipid oxidation capacity. The ability to lose weight is related to the capacity to oxidize fat. Thus, a relative defect in fat oxidation capacity is responsible for energy economy and hampered weight loss. Despite many herbs having both antidiabetic as well as antiobesity activity; there is no marketed formulation for obesity associated diabetes. The antidiabetic and antiobesity effect of the formulation was found to be nearly similar to that observed for glibenclamide and sibutramine respectively. It can be concluded that, the formulation should be considered as an excellent candidate for future studies of obesity associated diabetes.